Effects of HBsAg carriers on pregnancy complications in pregnant women: a retrospective cohort study - Weng, Mengqing; Wang, Jie; Yin, Jingfeng; Ren, Wenning; Wei, Caiping; Yang, Wenshan; He, Huimin (Frontiers in Medicine, 2023)
Objective: Hepatitis B virus (HBV) infection is a major health threat worldwide, especially in developing countries. We aimed to investigate the impact of hepatitis B carrier on pregnancy complications in pregnant women, in china. Methods: This retrospective cohort study was conducted by using data from the EHR system of Longhua District People's Hospital in Shenzhen, China, from January 2018 to June 2022. Binary logistic regression was used to evaluate the relationship between HBsAg carrier status and pregnancy complications and pregnancy outcomes. Results: The study included 2095 HBsAg carriers (exposed group) and 23019 normal pregnant women (unexposed group). Pregnant women in the exposed group were older than the pregnant women in the unexposed group (29 (27,32) vs. 29 (26,32), P < 0.001). In addition, the incidence of some adverse pregnancy complications in the exposure group was lower than that in the unexposed group, including hypothyroidism of pregnancy (adjusted odds ratio [aOR], 0.779; 95% confidence interval [CI] , 0.617-0.984; P = 0.036), hyperthyroidism of pregnancy (aOR, 0.388; 95% CI, 0.159-0.984; P = 0.038), pregnancy induced hypertension (aOR, 0.699; 95% CI , 0.551-0.887; P = 0.003), antepartum hemorrhage (aOR , 0.294; 95% CI, 0.093-0.929; P = 0.037). However, compared with the unexposed group, the exposed group had a higher risk of lower birth weight (aOR , 1.12; 95% CI, 1.02-1.23; P = 0.018) and intrahepatic cholestasis of pregnancy (aOR , 2.888, 95% CI , 2.207-3.780; P < 0.001). Conclusion: The prevalence rate of HBsAg carriers in pregnant women in Longhua District of Shenzhen was 8.34%. Compared with normal pregnant women, HBsAg carriers have a higher risk of ICP, a lower risk of gestational hypothyroidism and PIH, and a lower birth weight of their infants.